Drinking water behavior and willingness to use filters by middle-aged and elderly residents in rural areas: A cross-sectional study in Tengchong, China - Duan, Yuxin; Wu, Ruiheng; Ji, Haoqiang; Chen, Xu; Xu, Jia; Chen, Yunting; Sun, Meng; Pan, Yuanping; Zhou, Ling (Frontiers in Public Health, 2022)
Access to safe drinking water is critical to health and development issues, and residents' drinking behavior reflects their awareness of health and water hygiene. Random sampling and face-to-face questionnaires were used to investigate the drinking water behavior, sanitation and perceptions of drinking water among middle-aged and elderly residents in Tengchong, southwest Yunnan from July 1 to July 28, 2021. Differences between groups were assessed using the Chi-square test and t-test. Two binary logistic regression analyses were conducted to explore the influencing factors of drinking unboiled tap water and willingness to use filters. Results show that 35% of residents drink unboiled tap water, and 29.8% of respondents indicated a willingness to use filters. The model results showed a strong correlation between 60 and 79 years old (OR: 0.510, 95% CI: 0.303–0.858), 80 and above years old (OR: 0.118, 95% CI: 0.038–0.365), drinking water at a regular interval (OR: 0.397, 95% CI: 0.257–0.612), wanting to gain knowledge about drinking water (OR: 0.198, 95% CI: 0.099–0.395), Perceived health risks (PHR) (OR: 0.847, 95% CI: 0.771–0.929), having kidney stones (OR: 2.975, 95% CI: 1.708–5.253) and drinking unboiled tap water (p < 0.05). 60–79 years old (OR: 0.446, 95% CI: 0.244–0.815), 80 and above years old (OR: 0.228, 95% CI: 0.064–0.812), water storage (OR: 0.088, 95% CI: 0.026–0.300), middle school and above (OR: 2.238, 95% CI: 1.289–3.883), household water treatment (HWT) (OR: 33.704, 95% CI: 9.726–116.791), Perceived health risks (PHR) (OR:1.106, 95% CI: 1.009–1.213), water authority satisfaction (WAT) (OR:0.857, 95% CI: 0.769–0.956) and willingness to use filters were correlated (p < 0.05). Our findings suggested that a certain proportion of permanent middle-aged and elderly residents in rural areas still drink unboiled tap water, and residents are less willing to use filters. Residents' perception of drinking water can reflect residents' drinking water behavior and willingness to a certain extent. It is recommended that the government and Centers for Disease Control (CDC) should strengthen relevant measures such as knowledge popularization and health education, and regulate the water use behavior of middle-aged and elderly residents. Promote safe, economical and effective household water filtration facilities to ensure public health safety.